2019
DOI: 10.1002/slct.201901708
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of New Isatin‐Based QACs with High Antimicrobial Potency

Abstract: A simple and easy condensation reaction of aryl‐ or N‐substituted isatins with Girard's reagents P and T was found to be useful in obtaining of water‐soluble isatin‐based quaternary ammonium compounds (QACs) bearing pyridinium or trimethylammonium moiety with high yields. Their antimicrobial activity was evaluated. Selective activity against Gram‐positive bacteria (S. aureus 209p and B. cereus 8035) and yeast‐like fungus Candida albicans 855–653 was shown. The influence of the substituent's nature as in the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Bogdanov and colleagues explored the microbiological effect of isatin-based QACs (Figure 13) [62]. As seen from the figure, the structures of these ammonium 25 and pyridine 26-27 salts contain no long alkyl chains.…”
Section: Single-charged Qacs (Mono-qacs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Bogdanov and colleagues explored the microbiological effect of isatin-based QACs (Figure 13) [62]. As seen from the figure, the structures of these ammonium 25 and pyridine 26-27 salts contain no long alkyl chains.…”
Section: Single-charged Qacs (Mono-qacs)mentioning
confidence: 99%
“…Rusew and colleagues presented a work, in which long lipophilic tails in QACs were replaced by more compact aryl-containing substituents (Figure 14) [63]. Bogdanov and colleagues explored the microbiological effect of isatin-based QACs (Figure 13) [62]. As seen from the figure, the structures of these ammonium 25 and pyridine 26-27 salts contain no long alkyl chains.…”
Section: Single-charged Qacs (Mono-qacs)mentioning
confidence: 99%
“…, antioxidant (23), anti-tubercular (24), antifungal (25), anticonvulsant (26), antidepressant (27), anticancer (28,29), antiplasmodial activity (30), anti-corrosive (31), antiepileptic (32), antidiabetic (7) and antiviral (33) antianxiety (34), and antiasthma (35). In 1965, an isatin-2,3-dionebased compound Metisazone was developed, it is an antiviral agent used against viral infections as a prophylactic agent (36). Food and Drug Administration, USA (FDA) approved an isatin derivative Sunitinib maleate to treat different malignancies such as advanced renal-cell carcinoma, pancreatic neuroendocrine tumors and gastrointestinal stromal tumors (37,38).…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, the combination of a phenolic substituent, a hydrazone moiety and an ammonium center in one molecule will solve the problem of the solubility of the target compounds in water along with high antioxidant and antimicrobial activities. The development of this study is based on our ongoing work on the design, synthesis and evaluation of the biological activity of positively charged isatin‐3‐acylhydrazones, and spatially hindered phenols . Our previous results showed that compounds containing a bulky phenolic fragment showed the best activity against Staphylococcus aureus ( Figure ) …”
Section: Introductionmentioning
confidence: 99%